Brunbjörnars beteenderespons på hundträning : hur björnar (Ursus arctos) i hägn reagerar på hundträning - Roos Engström, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2020)
Dog training and testing on bears (Ursus arctos) occurs both on bears in the wild and bears in enclosures. In Sweden the main way of hunting bears is with dogs and the main cause of death of bears in Sweden is due to legal hunting. Today, to my knowledge, no research has been done on how bears in enclosures are affected by dog training. The aims of the present study were to investigate if bears show any behavioural signs of stress during dog training, if the training can be considered as enriching for the bears and if the bears’ behavioural response alters with the number of training episodes during the day and between training days. During dog training the bears at this training facility were kept in a test enclosure connected to their main enclosure. The bears were exposed to one dog at a time which is allowed to roam freely outside the test enclosure and bay and bark at the bears. Results showed that the bears’ response to dog training differs between individuals and that the dog training could be perceived as stressful for the bears. The bears displayed natural behaviours such as exploring and social interactions on all days of training, where social interactions mainly consisted of body contact. Behaviours related to stress such as charging towards the dog and moving away from the dog were shown by all individuals and pacing was exhibited by one of the bears. Social interactions such as playing was shown by two individuals once, but other behavioural responses did not indicate the dog training as a positive experience or as enriching for the bears. The behavioural response differed between number of practices and individuals but could not distinguish any behavioural patterns in the group. One of the bears showed pacing behaviour on the fourth training occasion of the day and two bears showed charging towards dog on the first observation of the day. This indicates that there are individual differences between the bears at this training facility. In conclusion, this study provided a picture of bears ...